2022
DOI: 10.1002/cne.25349
|View full text |Cite
|
Sign up to set email alerts
|

The brain of the tree pangolin (Manis tricuspis). IX. The pallial telencephalon

Abstract: A cyto‐, myelo‐, and chemoarchitectonic analysis of the pallial telencephalon of the tree pangolin is provided. As certain portions of the pallial telencephalon have been described previously (olfactory pallium, hippocampal formation, and amygdaloid complex), we focus on the claustrum and endopiriform nuclear complex, the white matter and white matter interstitial cells, and the areal organization of the cerebral cortex. Our analysis indicates that the organization of the pallial telencephalon of the tree pang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 90 publications
2
2
0
Order By: Relevance
“…It is worth noting that in another mammal with unusual skin, the tree pangolin, that layer 4 also appears to be atypical in that the neurons are pyramidalized and may in fact be the inner layer 3 noted herein, exhibiting a pattern of core thalamocortical projections like that noted in the cetaceans, hippopotamus, and elephant studied (Imam et al. 2022). The lamination of the neocortex in rhinoceroses and tapirs, both of which have skin that has a pachydermatous character (Cave and Allbrook 1959; Murie 1871; Plochocki et al.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…It is worth noting that in another mammal with unusual skin, the tree pangolin, that layer 4 also appears to be atypical in that the neurons are pyramidalized and may in fact be the inner layer 3 noted herein, exhibiting a pattern of core thalamocortical projections like that noted in the cetaceans, hippopotamus, and elephant studied (Imam et al. 2022). The lamination of the neocortex in rhinoceroses and tapirs, both of which have skin that has a pachydermatous character (Cave and Allbrook 1959; Murie 1871; Plochocki et al.…”
Section: Discussionsupporting
confidence: 50%
“…The skin and brain share an early ectodermal origin (Jameson, Boulton et al 2023); thus, perhaps alterations in the pattern/s and timing/s of gene/s expression/s leading to the development of unusual mammalian skin might have pleiotropic effects leading to the development of an atypical layer 4 and subsequent variation in the core thalamocortical projection laminar pattern. It is worth noting that in another mammal with unusual skin, the tree pangolin, that layer 4 also appears to be atypical in that the neurons are pyramidalized and may in fact be the inner layer 3 noted herein, exhibiting a pattern of core thalamocortical projections like that noted in the cetaceans, hippopotamus, and elephant studied (Imam et al 2022). The lamination of the neocortex in rhinoceroses and tapirs, both of which have skin that has a pachydermatous character (Cave and Allbrook 1959;Murie 1871;Plochocki et al 2017), is not yet known and thus cannot be compared here but would be of interest to determine (n.b., it has been reported that the domestic horse has a cytoarchitecturally distinct layer 4, Graïc et al 2022).…”
Section: Phylogenetic Aspects and The Evolution Of Variations In The ...supporting
confidence: 51%
“…In many mammals, like primates, cats, dogs, sheep, pigs, dolphins, echidnas, and to some extent rabbits, the CLCX is encapsulated by dense myelinated fibers both medially by the external capsule, and laterally by the extreme capsule (Ashwell et al., 2004 ; Buchanan & Johnson, 2011 ; Cozzi et al., 2014 ; Gattass et al., 2014 ; Kowianski et al., 1999 ; Pham et al., 2019 ; Pirone et al., 2021 , 2015 , 2018 ; Rahman & Baizer, 2007 ; Reynhout & Baizer, 1999 ; Wojcik et al., 2002 ). However, in animals like mice, rats, fruit bats, and pangolins, the extreme capsule is only rudimentary, making it difficult to located claustral borders by white matter alone (Bruguier et al., 2020 ; Imam et al., 2022 ; Kowianski et al., 1999 ; Morello et al., 2022 ; Orman et al., 2017 ). Moreover, it has been a longstanding challenge, in particular in the most commonly used rodent models, to define clear and robust schemes for potential subdivisions of the CLCX (Watson & Puelles, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Here, we finalize our series describing the anatomy of the central nervous system of the tree pangolin (Imam et al, 2017(Imam et al, , 2018a(Imam et al, , 2018b(Imam et al, , 2019a(Imam et al, , 2019b(Imam et al, , 2019c(Imam et al, , 2022a(Imam et al, , 2022b(Imam et al, , 2022c, by providing a detailed description of the external and internal anatomy of the spinal cord. Due to the foreshortening of the spinal cord of the tree pangolin (Imam et al, 2017), we employ a regional approach in this description, rather than the more commonly used vertebral level approach, as recommended by Sengul et al (2013) for comparative studies.…”
Section: Introductionmentioning
confidence: 99%